The Role Of Parents In Children's Independence When Memorizing The Al-Quran Online - Sergeev Robert; Glubb Ramachandran; Gonzales Armando (Yayasan Adra Karima Hubbi, 2023)
Parents play an active role in guiding their children to learn to memorize the Qur'an at home. Independence is an effort to remember the Qur'an during online learning. Moreover, the author conducted research at the Daratul Jannah Tahfiz House, Tanjung Barulak, Batipuh District. This research aims to foster children so that the role of parents can help children who have difficulty memorizing the Koran during online learning. The method used in this research is the descriptive qualitative method; moreover, the techniques used by researchers by using interviews, documentation, and observation. At the same time, the subjects of this research were parents and teachers. The results of this study at the Daratul Jannah Tahfiz House on Covid 19 have improved and are efficient. The number of those who deposited memorization to the teacher was ten people starting from the morning at 8.00 – 11.00. in memorizing Qur'an, parents play an active role in fostering children to learn the Qur'an. Moreover, parents control their children in online learning, and teachers also succeed in overcoming difficulties in children and provide facilities during online learning in remembering the Al-Qur'an; parents support their children in memorizing the Al-Qur'an and give appreciation.